The Existence of Cancellation of Grant in Religious Courts: A Legal Analysis and Maqashid Sharia of The Decision Number 6481/Pdt.G/2021/Pa.IM - Yusuf Agung Purnama; Slamet Firdaus (UIN Siber Syekh Nurjati Cirebon, 2025)
Grants are given to others with no hope of existence, reward, or whatever, and are done willingly, without counter-performance from the party that gives. The giver still lives. Grants cannot be cancelled except for the grant parent to child matter, as mentioned in the hadith of the Prophet, KUHPER, and the Compilation of Islamic Law. The purpose of this study is to analyse the juridical aspects of Islamic Law, Positive Law and Maqashid Syariah above the judge’s decision in the case number 6481/Pdt.G/2021/PA.IM regarding the case cancellation grant. The research method used by the author, which involves descriptive research , is one of the forms of research that includes qualitative research. The data used in the study are qualitative. Qualitative data, namely data presented in verbal form, is not in a numerical form. Among others, search and collect data with classification, including primary data and secondary data. In research, the author uses interviews, documentation and observation for data collection. The results of the research from the judge’s considerations in deciding case number 6481/PDT.G/2021/PA.IM regarding the case cancellation grant, the panel of judges’ opinion is that the lawsuit plaintiff must state No cannot be accepted. This is in accordance with Circular Letter Supreme Court Number 3 of 2018, letter A, number 4. In the formulation of the law of the religious chamber that the lawsuit whose object of dispute is still a debt guarantee and the judge does not use other legal considerations, in fact the judge in deciding a case should be based on the law and/or statutory regulations related to the lawsuit, such as Article 212 of the KHI which allows parents to withdraw their gifts and Article 1688 of the Civil Code.